The “Father’s Sons”: The Elite of the Kazan Khanate in the Lithuanian Metrica - V.V. Trepavlov (Золотоордынское обозрение)
Research objective: Analysis of the phrase otetskie deti (“father’s sons”) in the Register Book of the Lithuanian metrics (Lithuanian Metrica) as designations of the military service class of the Kazan khanate. Research materials: The 7th Register Book of the Lithuanian Metrica, Russian chronicles, the chronicles of Kïrïmi and Ötemish-Hajji, the works of S. Herberstein, A. Kurbsky, Maciej of Miechów, Mahmud al-Kashgari, A. Olearius. Results and novelty of the research: The 7th Register Book of the Lithuanian Metrics contains a translation of a message from the Crimean khan, Muhammad Giray, to the Polish King and Lithuanian Grand Duke Sigizmund I. In this letter, there is a reiteration of the requests of the inhabitants of the Kazan Khanate addressed to Muhammad Giray to send them one of his relatives to reign over them. The Kazanians wrote that they had twenty thousand otetskie deti (“father’s sons”) and countless Mordovians and Cheremisses, all of whom were ready to submit (to be “slaves”) to the ruler of the Crimea. The author of the article seeks the meaning of this term and looks for a putative Turkic equivalent to the expression otetskie deti as well as the reasons for the presence of the Mordovians and Cheremisses in this document. The word “otetskii” (paternal) had a wide range of usages in the Russian language of the 16th century – in the State of Muscovy and the Grand Duchy of Lithuania. One of its meanings was “belonging to an ancient, noble family”. The instances quoted by the author show a socio-cultural universality, which combined paternity, noble origin and elite status in a single notion. The author hypothesizes that the phrase “otetskie deti” in the Russian translation could replace the concept of “Tatars” in its social meaning, as a symbol of the military strata of the population of the Kazan khanate. Mention of the Mordovians and the Cheremisses in the Kazan message reflected the positive image of these peoples – namely, their high military reputation in neighboring countries. The Kazanians’ assurances to be ready to put two tumens of elite troops and crowded militia at the disposal of Crimea served as one of the stimuli for Muhammad Giray to assent to their request by dispatching Prince Giray to Kazan.